Production and characterization of protein extract from lempoyang ginger - Mellisa, Abdullah (2012)
Antimicrobial protein has received tremendous attention especially by the pharmaceutical industry,which sources mainly extracted from nature such as herbs and plants.These sources are known for their nontoxic property, biodegradable,as well as easily available in the market. Among the numerous natural resources,the Lempoyang ginger which scientifically known as Zingiber zerumbet L.Smith had long known for its application as antifungal,anti-inflammatory,anti-ulceration and antioxidant.It is also known for treating diarrhea,coughs,asthma and some other skin diseases.Lempoyang ginger is selected for this research as very few information was published on protein of this Zingiberaceae family of which among all,zerumbone was widely extracted as the major component.This research aimed to produce the protein extract from Lempoyang using the expanded bed adsorption chromatography(EBAC)and then characterize it using the sodium dodecylsulfate polyacrylamide gel electrophoresis(SDS-PAGE).The parameter that was varied for this research is the height of the bed settlement at 5cm,6cm,9cm and 11cm,with elution made in two-steps using 45% ethanol and 90% ethanol buffer solutions. Amberlite XAD7HP is used as adsorbents to bind the large complex protein molecules from Lempoyang feedstock with constant pump speed at 13rpm for each cycle.The eluted protein fractions are then subjected to Lowry‟s protein concentration determination technique before characterized for molecular weight determination using the SDS-PAGE tools. The dynamic binding capacity is determined from the 50% breakthrough of the initial feedstock solution,and the recovery ratio is determined for total protein obtained. From the results,protein concentration is higher when eluted with 45% ethanol buffer solution as protein were loosely bounded to the adsorbents while the first elution using 90% ethanol buffer solution showed a lower protein concentration.The washed protein and eluted protein fractions from EBAC which were tested on SDS-PAGE showed a protein band of eluted fraction protein band with molecular weight of 21.12 kDa.